Implementasi Layout Animasi 3d pada Gapura Tugu Masuk Wisata Bon Watu, Sambigede, Kecamatan Sumberpucung - Debytiantama, Gamaliel Brian; Andyko, Mohammad; Sulasmono, Raden Ian; Firdiansyah, Muhammad Hasan; Ansyorie, Mohammad Musthofa Al (Universitas Negeri Malang, 2024)
Sambigede Village is one of the villages located in the Administrative Area of Sumberpucung District, Malang Regency. As a village with a low area, Sambigede Village has many places that have the potential to be developed into a tourist village. Sambigede Village itself is a village located near the Karangkates Reservoir. This reservoir has the potential to be used as water tourism for tourists who come there. Tourists can visit various interesting potential tourist destinations. This makes Sambigede village an opportunity to develop into a tourist village. Several of these opportunities must be utilized to make Sambigede village more attractive to tourists. Exhibitions and the application of science and technology are thus necessary for the development of Sambigede village through digitizing the promotion and implementation of sustainable ecotourism. In this case, implementation development can be described as a general description of the master plan design and creation of the Sambigede village portal sign. The output intended for public service is the General Plan for the Water Tourism Village of Sambigede Village and also articles about the results of this activity are published in the community service magazine Sinta 5. This community service aims to obtain intellectual property rights in the form of copyright and to apply for patents and to obtain scientific-technical applied products within the framework of cooperation. or partnerships between communities and universities. Desa Sambigede merupakan salah satu desa yang terletak di Wilayah Administrasi Kecamatan Sumberpucung Kabupaten Malang. Sebagai desa dengan wilayah yang rendah, Desa Sambigede memiliki banyak tempat yang berpotensi untuk dikembangkan menjadi desa wisata. Desa Sambigede sendiri merupakan desa yang terletak di dekat Waduk Karangkates. Dimana waduk tersebut berpotensi untuk dijadikan wisata air bagi para wisatawan yang datang kesana. Wisatawan dapat mengunjungi berbagai destinasi wisata potensial yang menarik. Hal ini membuat desa Sambigede menjadi peluang untuk berkembang menjadi desa wisata. Beberapa peluang tersebut harus dimanfaatkan agar desa Sambigede semakin menarik bagi wisatawan. Pameran dan penerapan iptek dengan demikian diperlukan untuk pengembangan desa Sambigede melalui digitalisasi promosi dan implementasi ekowisata berkelanjutan. Dalam hal ini pengembangan implementasi dapat digambarkan sebagai gambaran umum tentang desain masterplain dan pembuatan plang portal desa Sambigede. Keluaran yang ditujukan untuk pelayanan publik adalah Rencana Umum Desa Wisata Air Desa Sambigede dan juga artikel tentang hasil kegiatan ini dimuat dalam majalah pengabdian masyarakat Sinta 5. Tujuan dari pengabdian masyarakat ini adalah untuk memperoleh hak kekayaan intelektual berupa hak cipta dan untuk mengajukan paten serta untuk mendapatkan produk terapan ilmiah-teknis dalam kerangka kerja sama. atau kemitraan antara masyarakat dan perguruan tinggi.